21st Century Sociology Learning: Integrating Digital Literacy, Collaboration, and Critical Thinking - Kartika, Rani; Putri, Annisa; Wita, Gusmira; Purnomo, Sigit (Juwara: Jurnal Wawasan dan Aksara, 2025)
The rapid transformation of global society in the digital age necessitates the integration of 21st century competencies in higher education, particularly in the field of sociology. This study investigates the effectiveness of integrating digital literacy, collaborative learning, and critical thinking into sociology education among undergraduate students. A descriptive quantitative method was employed, involving 35 students from the Sociology Education Study Program at a public university in Indonesia. Data were collected through a validated Likert-scale questionnaire comprising 30 items across three core constructs. Descriptive statistical analysis revealed that students perceived the integration of these competencies to be highly effective. Digital literacy scored a mean of 4.31 (SD = 0.46), collaborative learning 4.25 (SD = 0.52), and critical thinking 4.37 (SD = 0.48), all categorized as “very high.” The overall average score was 4.31, corresponding to 86.2% in percentage agreement. These findings suggest that the learning model successfully fosters essential 21st century skills, equipping students with digital fluency, social collaboration, and analytical capacity in the context of sociological inquiry. The study concludes that a purposeful pedagogical design embedding these three competencies enhances students’ academic engagement and critical sociological understanding. It also calls for broader implementation and further research to explore long-term impacts and institutional scalability of 21st century learning frameworks in higher education.